2021
DOI: 10.1016/j.heliyon.2021.e08236
|View full text |Cite
|
Sign up to set email alerts
|

Communication factors influencing adoption of soil and water conservation technologies in the dry zones of Tharaka-Nithi County, Kenya

Abstract: Integrated soil fertility and soil water conservation technologies are possible solutions to the low per capita food production in Sub-Saharan Africa (SSA). Nonetheless, the rate of adoption of these technologies by smallholder farmers has stagnated over the years despite being recommended. This has been attributed to the existence of wide communication gaps among researchers, extension agents, and farmers. Therefore, this study aimed to assess the influence of communication factors on the adoption of the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Knowledge based on local wisdom from generation to generation becomes a worthy innovation to continue to be developed. Communication and knowledge sharing are essential in the adoption and sustainability of any innovation (Njenga et al, 2021). Tradition, customary law and the existence of customary leaders play an important role as a communication symbol for the compliance of community members in preserving the forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge based on local wisdom from generation to generation becomes a worthy innovation to continue to be developed. Communication and knowledge sharing are essential in the adoption and sustainability of any innovation (Njenga et al, 2021). Tradition, customary law and the existence of customary leaders play an important role as a communication symbol for the compliance of community members in preserving the forest.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of tourism communication and environmental communication spreads messages containing the importance of protecting the environment but on the other hand spreading tourism that can improve people's welfare. Communication and knowledge sharing are very important in the adoption and sustainability of any development innovation in society (Njenga et al, 2021). Revitalization in customary values is important as mandated by Law Number 5 of 2017 concerning the Advancement of Culture.…”
Section: Fig 4: Environmental Communication Model For Forest Conserva...mentioning
confidence: 99%
“…Training is one of the critical means of acquiring, developing and assimilating diverse agricultural techniques which ultimately impart positive behaviour and attitude on the impact of agricultural technologies (Lukuyu et al, 2012;Macharia et al, 2014). Additionally, training is vital in imparting knowledge and sensitizing farmers on productivity effects and environmental concerns of agricultural technologies (Njenga, Mugwe, Mogaka, et al, 2021;Njenga, Mugwe, Nyabuga, et al, 2021). The findings by Danquah et al (2019) has shown that farmers who have frequent contact with training programs are likely to adopt agricultural technologies, attributing a similar aspect in adoption intensity.…”
Section: Reject Technologiementioning
confidence: 99%
“…About 80% of the total population depend on the sector for survival and it contributes up to 25% on gross domestic product (GDP) globally (WorldBank, 2021). Despite its economic significance, the sector faces a number of drawbacks on resource utilization because of population pressure and climate change (Ghosh, 2019;Njenga, Mugwe, Mogaka, et al, 2021;Njenga, Mugwe, Nyabuga, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Darkwah et al (2019) indicated that farmers could be trained to raise awareness and support the adoption of modern technologies. According to Njenga et al (2021), training provides farmers with a platform for queries and justifications.…”
Section: Determinants Of Participation In Soil and Water Conservationmentioning
confidence: 99%